Effect of SNS addiction on prosocial behavior: mediation effect of fear of missing out - Xu, Manjing; Liu, Donglin; Yan, Jinzhe (Frontiers in Psychology, 2024)
Purpose-This study examines the relationship between social networking sites addiction and pro-social behavior, considering the increasing importance of social networking sites in daily life. It explores the mediating role of Fear of Missing Out in this relationship and investigates the moderating role of basic psychological need satisfaction. Research design, data, and methodology: This study employed a snowball sampling method to conduct an online survey among social network users in China. The proposed model was tested using regression analysis to interpret the results. Results-Findings indicate a negative predictive effect of social networking sites addiction on prosocial behavior. Misplaced fear partially mediates this relationship. Basic psychological need satisfaction significantly moderates the mediating effect of Fear of Missing Out on the relationship between SNS addiction and prosocial behavior. Practical implications-This study provides strategies for effectively preventing social networking sites addiction in real-world settings and mitigating its negative impact on individuals’ physical and mental health. It suggests interventions at four levels—individual, school, society, and government—to enhance basic psychological need satisfaction, thereby improving prosocial behavior and facilitating the promotion of interpersonal interactions and the equitable, harmonious development of society. Keywords social networking sites addiction, Fear of Missing Out, basic psychological need satisfaction, prosocial behavior